Transforming public service delivery in Bangladesh: The impact of G2P approach - Md. Rakibul Islam; Aditi Sarker (Department of Government Science, 2025)
In the digitized phase of Bangladesh, the government-to-person (G2P) approach represents an innovative shift in public service delivery. This model transforms the traditional